Materials development for TESOL - Mishan, Freda; Timmis, Ivor (Edinburgh textbooks in TESOL., 2015)
The fundamental principles of materials development in TESOL. Materials are at the very centre of language teaching, and understanding what goes into creating them is an essential part of a language teacher's professional development. Offering a practical introduction to the fundamental principles of materials development in TESOL, this textbook introduces you to a wide range of theoretical and practical issues in materials development to enable you to make informed and principled choices in the selection, evaluation, adaptation and production of materials. Advocating a principled approach to the creation of materials, it combines an awareness of relevant language learning and teaching theory with a critical attitude to existing published materials. It also encourages critical reflection by demonstrating how choices need to be informed by an awareness of culture, context and purpose. Material Development in TESOL's stimulating approach, with thought-provoking, interactive tasks, online resources, and added perspectives from international research, makes it an ideal textbook for language teacher programmes around the world, equipping TESOL student teachers and practicing teachers with the frameworks, resources and practical skills necessary to carry out effective evaluations and to develop principled materials in practice. Written specifically for TESOL practitioners and those studying TESOL teaching Accessible presentation of concepts and research Accompanying website provides additional online resources and materials Interactive tasks and further reading suggestions Encourages students to critically reflect on their choices of materials